STRENGTHENING TEACHER COMPETENCE THROUGH WRITING ISLAMIC RELIGIOUS EDUCATION TEXTBOOKS IN SCHOOLS/MADRASAH BASED ON ISLAMIC BOARDING SCHOOLS: Penguatan Kompetensi Guru Melalui Penulisan Buku Ajar Pendidikan Agama Islam pada Sekolah/Madrasah Berbasis Pesantren - gunawan, heri; Hidayat, Heri; Hilmi, Fuad (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Strengthening teacher competency is one of the strategic efforts in improving the quality of learning, especially in Islamic Religious Education (PAI) in Islamic boarding schools/madrasas. This Community Service (PkM) activity aims to improve teachers’ ability to write PAI textbooks that are contextual, systematic, and appropriate to the characteristics of the Islamic boarding school environment. The method used is the Asset Based Community Development (ABCD) approach, which focuses on developing the potential and assets that teachers already have, especially in the fields of literacy and writing. The activity was carried out in the form of seminars and mentoring by involving expert resource persons in the field of textbook writing. Partners in this activity were Uncip Tasikmalaya as the venue provider and IRMA West Java Tasikmalaya region as the provider of participants. The results of the activity showed an increase in teachers’ understanding and skills in compiling PAI textbooks, as well as the preparation of textbook drafts that are relevant to learning needs in the Islamic boarding school environment. Thus, this activity is expected to contribute to improving the quality of PAI learning through strengthening teachers’ professional competencies.